Effect of Aquarobic and Weight Training on Cortisol Levels in Obese Women - Mukarromah, Siti Baitul; Susanto, Hardhono; Rahayu, Tandiyo (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2016)
Exercise is physical stress which potentially causes disruption of homeostasis, especially in sports that is excessively done. Weight Training (LB) and Aquarobic Exercise (LA) can be modulators of handling stress. This research aims at investigating the effect of the difference between LB and LA to physical stress in obese women. The study was conducted in 2014. The method used in this study was randomized experimental pretest-posttest control group design in 36 obese women, aged 45-50 years who were divided into 3 groups, group LB 50% RM, 3 sets, 12 repetition, treatment two times a day for 8 weeks (n = 12), LA 75% HRmax, treatment 2 days for 8 weeks (n = 12) and control group (n = 12). Body Mass Index (BMI) and cortisol levels were measured before and after the treatment. Hypothesis testing was conducted using test (One-Way ANOVA and Kruskal-Wallis) and the mean difference test (Tukey HSD and Mann Whitney’s). The results of BMI is increased in the WT group and is decreased in LA group as compared to control group (p <0.05). The decrease of cortisol level is higher than in LA and LB group and controls (p <0.05). LB and LA affect the physical stress that is characterized by the increase in cortisol levels in obese women. Conclusion: LB is more dominant than LA in increasing physical stress.